Reading vs understanding the qur’an: a survey - Sulaiman, Kabuye Uthman (s.n, 2012)
The Qur’Én is the basis of Islam and an intrinsic part of a Muslim life.1 It is the strong rope that connects Muslims to their Lord, Allah, the Straight Path (al-ØirÉt al-MustaqÊm)leading them to everlasting bliss and the backbone of their success in both existences, i.e. al-DunyÉ and al-Ókhirah (here and hereafter).2 The purpose of this paper is twofold: first, to explore how Muslims read the Qur’Én and second, to make recommendations on how the Qur’Én should be read. It is undeniable that recitation of the Qur’Én is an activity in which Muslims engage from childhood to death. No day passes without the Qur’Én being read. It is not an exaggeration to say that the minimum number a Muslim is required to read the Qur’Én a day is seventeen times. Despite this, however, it is unfortunate that not many Muslims understand what they read from the Qur’Én!3 In the concluding remarks the researcher contends that understanding the Qur’Én is essential if Muslims are to uplift themselves from the current state of moral, spiritual, political and economic decline; that understanding the Qur’Én is amr (a commanded duty)4 based on Qur’Énic verses and ÍadÊth. This means that every Muslim is under a religious obligation to understand the Qur’Én; that knowledge of Arabic is a complimentary and not a necessary requirement to understand the Qur’Én; that Muslims would have been the leaders of the world today had they been able to continue dealing with the Qur’Én the way it was dealt with by the Prophet’s companions and their immediate successors; finally, understanding the Qur’Én is the greatest challenge facing Muslims today.